Genetic Diversity, Heritability and Agronomic Traits of Upland Rice Cultivars - Sakka Samudin; Mustakim Mustakim; Mustamin Mustamin; Maemunah Maemunah (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
The Indonesian archipelago boasts a rich biodiversity, particularly a vast collection of local upland rice germplasm, many of which remain unidentified. The study aimed to expand the collection of local rice germplasm by considering the genetic variability coefficient and heritability values and identifying cultivars with the potential to become superior local varieties. The research was conducted in Tamarenja Village from April to October 2024. The study used a single - factor randomized block design with eight cultivars as treatments, including Pae Bohe, Kalendeng, Delima, Pulu Tau Leru, Dongan, Wangga, Logi, Tako, Buncaili, Uva, Uva Buya, and Jahara. The collected data were analyzed using variance analysis, genetic variability coefficient analysis, heritability, and agronomic trait analysis using the LSD test at a 1% significance level. The results showed high genetic diversity, with genetic coefficient of variation (GCV) values between 24.56% and 53.49%. Estimates of heritability were also high, with most characteristics having more than 80% heritability. Grain yield (97.93%), number of grains per panicle (95.87%), and 1000-grain weight (97.49%) were all strongly controlled by genetics. Delima exhibited the longest panicle at 38.55 cm, containing 260 grains per panicle. The results identify Jahara, Kalendeng, Dongan, Logi, and Uva Buya as exceptional cultivars with considerable potential for upland rice breeding.